The News of the Covid-19 Vaccine in the Media and Public Resistance in Indonesia: A Study of Islamic Law - Sangaji, Ruslan; Basri, Halimah; Wandi, Wandi; Sultan, Muslihin; Rasyid, Nirwana (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2021)
This article aims to examine media coverage of COVID-19 and the resistance of the Indonesian people. This research is a legal sociology study that discusses the public's response to government policies regarding the Covid-19 vaccine with an Islamic legal approach. The data is analyzed using critical discourse analysis. This study concludes that community resistance to vaccines has a relationship with online media content. News content of victims who died after the vaccine, information about vaccines that impact the human body to become sick in the long term, and information about raw materials or contents of the Covid-19 vaccine that are not halal, indirectly have implications for the community resistance. This refusal was mainly due to information about victims who had been vaccinated experienced vaccine failures, especially from social media such as YouTube, WhatsApp, and Facebook, which are sometimes difficult to justify. According to Islamic law, people should be careful about content and news regarding Covid-19 because it may not be accurate. Therefore, the government needs to provide solutions in various ways. First, the government oversees all social media in conveying information so that all news related to the COVID-19 vaccine needs to be more careful and wisely not to worry the public. Second, the government needs to re-strengthen media regulations or news coverage that doesn’t seem to work optimally. Moreover, the government's vaccine policy aims to prevent the danger of the virus, which guarantees the safety of people's lives, and it is part of maqâshid al-syarī'ah. Likewise, the government has involved the MUI, which has authority in the field of religious fatwas, so that the certainty that the vaccine is halal can be accounted for in Islamic law.